2015
DOI: 10.1111/bcpt.12511
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Ciprofloxacin on the β‐Glucuronidase‐mediated Deconjugation of the Irinotecan Metabolite SN‐38‐G

Abstract: Abstract:The enterohepatic recycling of a drug consists of its biliary excretion and intestinal reabsorption, which is sometimes accompanied by hepatic conjugation and intestinal deconjugation reactions. b-Glucuronidase, an intestinal bacteria-produced enzyme, can break the bond between a biliary excreted drug and glucuronic acid. Antibiotics such as ciprofloxacin can reduce the enterohepatic recycling of glucuronide-conjugated drugs. In this study, we established an in vitro system to evaluate the b-glucuroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…A previous study showed that ciprofloxacin inhibited the hydrolysis of mycophenolic acid glucuronide to mycophenolic acid by inhibiting β-glucuronidase [17] . A recent study demonstrated an inhibitory effect of ciprofloxacin on the β-glucuronidase-mediated deconjugation of the irinotecan metabolite SN-38-G [33] . The present study also showed that the β-glucuronidase activity gradually increased along the proximal small intestine toward the ileal valve in CON rats.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that ciprofloxacin inhibited the hydrolysis of mycophenolic acid glucuronide to mycophenolic acid by inhibiting β-glucuronidase [17] . A recent study demonstrated an inhibitory effect of ciprofloxacin on the β-glucuronidase-mediated deconjugation of the irinotecan metabolite SN-38-G [33] . The present study also showed that the β-glucuronidase activity gradually increased along the proximal small intestine toward the ileal valve in CON rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the bacterial enzyme contains a 'bacterial loop' not found in the human form of the enzyme, enabling highly selective inhibitors of the bacterial enzyme to be developed, two of which blocked the active site of the E. coli β-glucuronidase, but had no effect on bovine liver glucuronidase. The quinolone antibiotic ciprofloxacin has also been shown to inhibit this enzyme, and low doses of amoxapine, a known inhibitor of bacterial β-glucuronidases, suppressed diarrhoea associated with irinotecan in a rat model 46,47 . An analysis of crystal structures of representative β-…”
Section: [H1] Microbial Enzymatic Degradation and Metabolismmentioning
confidence: 99%
“…However, gut microbes are not always beneficial. An increased understanding of gut microbial metabolism has revealed contributions to drug toxicity such as mucositis and neuropathy that can even prove fatal [ 22 , 23 , 25 , 26 , 43 ]. The delicate equilibrium of bacterial community structure and host-microbiota interactions is also disrupted by chemotherapeutic administration, which promotes inflammation and mucosal destruction, and is associated with adverse outcome [ 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome characterisation may, therefore, identify patients at risk of irinotecan-induced mucositis while manipulation of the microbiota may provide novel therapeutic options. Ciprofloxacin and low doses of amoxapine have been shown to be effective in the suppression of bacterial ß-glucuronidase activity and mucositis [ 22 , 23 ]. Furthermore, bacterial ß-glucuronidases possess unique motifs relative to their human counterparts, which pave the way for the development of bacterial-specific inhibitors [ 22 24 ].…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation